On the dynamical equations of a system of linearly coupled nonlinear oscillators - Bak, S. N.; Pankov, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We consider a system of differential equations that describes the dynamics of an infinite chain of linearly coupled nonlinear oscillators. Some results concerning the existence and uniqueness of global solutions of the Cauchy problem are obtained.